Examining Customer Satisfaction and Service Quality in Online Food Delivery: Evidence from Malaysia - Anees Jane Ali; Rosmelisa Yusof; Hui Shan Mok; Mohammad Farhan Basim; Mohd Nasim Bin Naseer Ahmad; Mohd Zulhairi Bin Saadin; Muhammad Adam Danial Bin Yusrin; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
Online food delivery platforms have significantly transformed customer experiences in Malaysia, particularly during and after the COVID-19 pandemic. This study aims to examine the key determinants influencing customer satisfaction toward Foodpanda services in Malaysia. A quantitative research design was employed, and data were collected from 200 respondents through an online survey. Using multiple linear regression with SPSS, the results indicate that trust (? = 0.318, p 0.001), perceived usefulness (? = 0.293, p 0.001), and price fairness (? = 0.292, p 0.001) have significant positive effects on customer satisfaction. Meanwhile, convenience (? = 0.013) and service quality (? = 0.061) show no significant influence. The model demonstrates strong explanatory power, with R² = 0.788 and an F-statistic of 149.272 (p 0.001). These findings highlight that customer satisfaction in online food delivery is primarily driven by trust, perceived usefulness, and fair pricing. The study extends the Technology Acceptance Model (TAM) and offers managerial implications for enhancing digital service reliability, platform security, and pricing transparency.